Design and synthesis of phenyl silicone rubber with functional epoxy groups through anionic copolymerization and subsequent epoxidation. (9th January 2020) - Wang, Yimin; Cao, Renwei; Wang, Meihao; Liu, Xiaomin; Zhao, Xiuying; Lu, Yonglai; Feng, Anchao; Zhang, Liqun
Abstract: In this paper, we have developed epoxidized phenyl silicone rubber (EMVPQ) with good oil and radiation resistance by anionic ring-opening copolymerization and further epoxidation modification. Silicone rubbers with both phenyl and epoxy groups were firstly synthesized and main properties of the material were characterized. When the phenyl content in EMVPQ was increased from 5% to 20%, the damping loss peak shifted to the high temperature by 36 °C and the effective damping temperature range was widened by 3 °C. The tensile strength of EMVPQ with 20% phenyl content did not change before and after irradiation. When the epoxy content is only 13%, the EMVPQ retained mechanical properties after immersion at 25 °C or 100 °C for 72 h, but a commercial sample substantially lost its mechanical properties. This work not only promotes the research of epoxidized phenyl silicone rubber, but also opens an effective way for the preparation of high-performance aerospace materials. Graphical abstract: Image 1 Highlights: We firstly designed and synthesized a silicone rubber with both phenyl and epoxy groups. The epoxidized phenyl silicone rubber exhibit significant advantages over most existing silicone rubber. Epoxidized phenyl silicone rubber is more conducive to the stability of the material under high temperature conditions. Epoxidized phenyl silicone rubber has good oil resistance at 100 °C. The introduction of phenyl and epoxy groups has a greater effect on radiation resistance.